" Block Chain Technology in Global Trade in Finance " (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Blockchain technology has emerged as a foundational digital infrastructure capable of redefining global trade and financial ecosystems through its decentralized, immutable, and trust‐enhancing architecture. By eliminating conventional intermediaries and reducing informational asymmetries, blockchain strengthens transactional transparency, accelerates cross-border settlements, and enhances the authenticity of trade documentation. Its applications including distributed ledgers for supply chain traceability, smart contracts for automated trade finance, and digital identities for customs and compliance are enabling unprecedented operational efficiencies across international logistics and regulatory environments.In the financial domain, blockchain facilitates secure and near-instantaneous value transfers, supports innovative instruments such as asset tokenization, and expands financial accessibility through decentralized finance (DeFi). Central bank digital currencies (CBDCs) further signal a structural transformation in global monetary governance by promoting interoperability and reducing systemic frictions. Despite such transformative potential, significant challenges remain: fragmented regulatory frameworks, scalability constraints, cybersecurity concerns, and the need for harmonized global standards.This study critically evaluates blockchain’s multi-dimensional impact on international trade and financial systems, examining its strategic advantages, evolving use cases, and institutional implications. The analysis underscores that long-term global adoption will require coordinated policy reforms, cross-border regulatory convergence, and robust technological infrastructure. The findings aim to contribute to international scholarly discourse by mapping blockchain’s trajectory as a catalyst for a more transparent, resilient, and integrated global economic order.